Holistiese verstaan teenoor analitiese verstaan in Bybelse hermeneutiek - Niekerk, B. van (Hervormde teologiese studies, 1991)
Holistic interpretation compared to analytical interpretation in biblical hermeneutics In recent years there has been growing interest in a holistic approach to biblical hermeneutics. If this holistic approach leads us to a new, post-critical, macro-paradigmatic model, the concequences for hermeneutics - indeed for theology as a whole - should be examined. Mechanism and holism should be explained in terms of each other, to compare their possible advantages and disadvantages. Finally, the relevance of Christianity amid changing visions of reality is discussed.